The influence of museum experience on revisit intention at Museum Sri Baduga - Nafisa Rani Anindita; Maulana Maulana; Irena Novarlia (Indonesia Accounting Research Journal, 2025)
The primary objective of this research is to examine and quantify the influence of museum experience on tourists’ intention to revisit Museum Sri Baduga, Bandung. The research was motivated by the rise in Indonesia’s tourism ranking, which has not translated into increased museum visitation rates. While prior research has demonstrated the role of museum experience in generating visitor satisfaction, there remains a gap in understanding how satisfaction affects behavioral loyalty. This research employed a quantitative approach using survey data collected from 106 tourists aged 17 years and above between March and April 2025. A simple linear regression analysis revealed that museum experience explained 74% of the variance in revisit intention, with celebrative experience emerging as the most influential dimension. Findings indicated that most satisfied visitors prefer recommending the museum to others over repeat visits, highlighting a disconnect between satisfaction and return intention. The study concluded that improving social interactivity, immersive programming, and tour guide quality may enhance engagement and encourage sustained visitation.